2000
DOI: 10.1128/jb.182.7.1872-1882.2000
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Factors Independently RegulatehilAand Invasion Gene Expression inSalmonella entericaSerovar Typhimurium

Abstract: HilA activates the expression of Salmonella enterica serovar Typhimurium invasion genes. To learn more about regulation of hilA, we isolated Tn5 mutants exhibiting reduced hilA and/or invasion gene expression. In addition to expected mutations, we identified Tn5 insertions in pstS, fadD, flhD, flhC, and fliA. Analysis of the pstS mutant indicates that hilA and invasion genes are repressed by the response regulator PhoB in the absence of the Pst high-affinity inorganic phosphate uptake system. This system is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
241
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(250 citation statements)
references
References 81 publications
8
241
1
Order By: Relevance
“…Analysis of hilA-lacZ transcriptional fusions by Lee and colleagues (30)(31)(32)42), among others, led to a model proposing that hilA transcription is repressed by a negative factor acting within the promoter region between positions Ϫ300 and Ϫ100. The HilD and perhaps the HilC proteins play central roles in controlling hilA transcription and may counteract this repressor activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of hilA-lacZ transcriptional fusions by Lee and colleagues (30)(31)(32)42), among others, led to a model proposing that hilA transcription is repressed by a negative factor acting within the promoter region between positions Ϫ300 and Ϫ100. The HilD and perhaps the HilC proteins play central roles in controlling hilA transcription and may counteract this repressor activity.…”
Section: Discussionmentioning
confidence: 99%
“…4, lane 1) and from an isogenic mutant deleted for SPI1 (Fig. 4, lane 2) grown under inducing conditions for hilA expression, i.e., high salt and low aeration (32). A single SPI1-dependent transcript was detected for hilC and hilD.…”
Section: Purification and Activity Of Recombinantmentioning
confidence: 99%
See 1 more Smart Citation
“…Another insight from the model is the prediction that FliZ is the secretiondependent link between flagella and the SPI1 regulatory network. FliZ has been previously shown to be activator of SPI1 gene expression, and our model predicts that this happens post-secretion (Chubiz et al 2010;Iyoda et al 2001;Lucas et al 2000). Previous modeling efforts of the flagellar regulon have been limited to the FliA-FlgM interaction only (Kalir et al 2005;Saini et al 2011).…”
Section: Discussionmentioning
confidence: 59%
“…In addition, Fur affects iron uptake by binding to the promoter region of ironregulated genes with ferrous iron as a cofactor, thus repressing the expression of these genes (Hantke, 2001). The virulence and pathogenesis of medically important organisms are also regulated by these regulators, and in recent years great progress has been made in identifying those that coordinate expression of virulence genes (Byrne & Swanson, 1998;Johnson et al, 2006a;Lucas et al, 2000;Mellies et al, 2006;Pizarro-Cerda & Tedin, 2004). Perhaps not surprisingly, such regulators are almost as numerous as the environmental signals to which virulence gene expression has been found to respond (Dong et al, 2005;Lucas & Lee, 2001;Sturme et al, 2005), and many of them remain to be identified.…”
Section: Introductionmentioning
confidence: 99%